A novel green and low friction composite reinforced by lignum vitae chips. (November 2022) - Wu, Yuhang; Dong, Conglin; Bai, Xiuqin; Yuan, Chengqing; Zhang, Xiangjun
Abstract: Lignum vitae was widely applied in water-lubricated bearing because of its green, pollution-free, excellent mechanical, and self-lubricating properties. The slow growth cycle is difficult to meet the bearing's rapid development. Lignum vitae chips were used to modify thermoplastic polyurethane (TPU) to extend its good self-lubricating properties and improve tribological behaviors. The results showed that lignum vitae improve TPU's shore hardness, elastic modulus, and elongation, but at the slight cost of tensile strength and thermal stability. Besides, lignum vitae chips endowed TPU with good hydrophilicity and water absorption properties, which conduced to form effective lubricating film and reduced COF behaviors. TPU with 6% lignum vitae chips had the best COF reduction and wear resistance. But excessive lignum vitae chips weakened elastic modulus and elongation to increase COF behaviors and wear process. The outcome obtained herein would provide strong theoretical guidance for developing novel green and sustainable composites with excellent tribological properties. Highlights: A novel green TPU matrix water-lubricated bearing was fabricated by adding lignum vitae chips. Lignum vitae possessed many polar bonds and hydrophilic functional groups. Lignum vitae chips endow TPU with hydrophilicity and excellent water absorption properties. TPU with 6 wt% lignum vitae chips presented the best COF reduction and wear resistance.